Drug-loaded hybrid hydrogels for sonodynamic-chemodyanmic therapy and tumor metastasis suppression - Wang, Xiaoying; Zhu, Liyun; Zhou, Jianhui; Zhao, Lingzhou; Li, Jingchao; Liu, Changcun (Frontiers in Bioengineering and Biotechnology, 2023)
Although various therapies have been adopted to treat cancer, metastasis of tumor cells still is a big challenge that compromises therapeutic benefits. We herein report an injectable drug-loaded hybrid hydrogel that can achieve sonodynamic therapy (SDT) and chemodyanmic therapy (CDT) combined action and suppression of tumor metastasis. This alginate (ALG)-based hydrogel (termed as AMPS) contains manganese dioxide (MnO2) nanoparticles as the CDT agents, an organic polymer as the sonosensitizer, and a SIS3 drug as metastasis inhibitor. AMPS is formed via the chelation of ALG by Ca 2+ in tumor microenvironment, in which MnO2 nanoparticles mediate CDT via Fenton-like reaction and the organic polymers enable SDT under ultrasound (US) irradiation by generating singlet oxygen ( 1 O2), allowing for combinational action of CDT and SDT. In addition, SIS3 is released from AMPS hydrogels to inhibit the metastasis of tumor cells. As such, the AMPS enables a combinational action of SDT and CDT to greatly inhibit the growths of subcutaneous tumors in living mice and also completely suppress the tumor metastasis in lungs and livers. This study thus offers a hybrid hydrogel platform for combinational therapy and metastasis suppression simultaneously.